Legal Policy of Education Budget Allocation in Digitalization Policy through Procurement of Technological Devices to Fulfill Children' Constitutional Rights to Legal Literacy at Elementary Education Level - Beby Savitri; Evita Isretno Israhadi (CV. Green Publisher Indonesia, 2026)
This study aims to analyze the legal politics of education budget allocation within the digitalization policy and its implications for fulfilling children's constitutional rights to legal literacy at the primary education level. Through an examination of the Republic of Indonesia's 1945 Constitution, Law Number 20 of 2003 concerning the National Education System, and Law Number 35 of 2014 concerning Child Protection, the study used a normative juridical method with a statutory and conceptual approach, and regulations related to state finances. The results indicate that the educational digitalization policy, which focuses on the procurement of technological devices, is not completely aligned with the constitutional mandate, as it tends to neglect strengthening human resource capacity and children's legal literacy. This situation constructs a gap between legal norms and policy implementation, and has implications for children's low legal awareness and an increased risk of legal violations. Therefore, a reconstruction of the legal politics of education is needed through strengthening regulations, reforming budget policies, and integrating legal literacy into the primary education curriculum to ensure the optimal fulfillment of children's constitutional rights